2020
DOI: 10.1103/physrevfluids.5.073101
|View full text |Cite
|
Sign up to set email alerts
|

Doing more with less: The flagellar end piece enhances the propulsive effectiveness of human spermatozoa

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 40 publications
(40 reference statements)
2
35
0
Order By: Relevance
“…With such extensive flagellar detail captured, we consider the previously unavailable metric of maximal distal curvature (MDC), suggested by Neal et al [ 16 ] to be correlated with swimming efficiency. We compute the MDC of each of the swimmers throughout their beat, as described in the Methods and material, which are shown as histograms in figure 5 c stratified by sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With such extensive flagellar detail captured, we consider the previously unavailable metric of maximal distal curvature (MDC), suggested by Neal et al [ 16 ] to be correlated with swimming efficiency. We compute the MDC of each of the swimmers throughout their beat, as described in the Methods and material, which are shown as histograms in figure 5 c stratified by sample.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the expansion into near-complete planar flagellar waveform capture offers the prospect of novel directions for the exploration of male gamete motility, and flagellated or ciliated organisms more generally. The significance of high-fidelity analysis of flagella is further highlighted by the recent work of Neal et al [ 16 ], with the overall efficiency of a spermatozoon suggested to be linked to distal curvature. Measurement of such curvatures requires the capture of large proportions of the flagellum, greater than previously available en masse with readily accessible microscopy as demonstrated here to be achievable on significant sample sizes, though with further developments in imaging and subsequent image processing required to capture complete details of the distal flagellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With force density a fundamental component of such elastohydrodynamic frameworks, these apparent errors may contribute non-negligibly to the simulated dynamics and applications, particularly given the reported significance of distal activity in recent model spermatozoa (Neal et al. 2020). Thus, the absence of comparable oscillations in the RNS solutions represents a significant advantage over these existing methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…(2019) to include improved non-local hydrodynamics, applied to the model biological problem of flagellar efficiency (Neal et al. 2020), and extended to motion in three dimensions (Walker, Ishimoto & Gaffney 2020 b ).…”
Section: Introductionmentioning
confidence: 99%